Theory of stewardship in the marriage of female migrant workers: Perspectives of accounting and accountability - Febrina Nur Ramadhani; Lilik Purwanti; Aji Dedi Mulawarman (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2021)
This research explores accounting and accountability practices in the families of female workers (TKW) in East Java, based on the concept of stewardship theory. The study was carried out using a qualitative approach to ethnomethodology; we obtained data on 10 TKW individuals from East Java through in-depth interviews with the FGD technique. The results show that, based on the concept of stewardship theory, the implementation of accounting and accountability practices in TKW families has been applied. In TKW families, accounting and accountability practices aim to control the financial management of the husband's family so that it does not exceed the budget set by the wife and there is no deviation in the use of funds. This study shows that the application of the concept of stewardship theory can avoid various disputes that may arise due to problems of accountability for financial management. The application of the concept of stewardship theory, on the other hand, affects accounting practices that pay attention only to material aspects to lead TKW families to the spirit of capitalism.